Augmented reality in the teaching of natural sciences - Torres Oliveros, Silvia Andrea; Bustamante Meza, Lucia (I+ T+ C- Research, Technology and Science, 2019)
The present article, the result of a research project describes the results around the implementation of a didactic resource based on augmented reality in the area of natural sciences of the fifth grade of primary of the Rodrigo de Bastidas District Educational Institution. The main objective of the project was to implement a teaching resource based on Augmented Reality (AR) in the area of natural sciences, this was achieved following the focus of action research using booklets aimed at the teacher and students in which they were visualized 2D and 3D images referring to the sense organs, given that this subject is part of the content of the Natural Sciences area. As a main result, educational innovation stands out through the interaction of students with the material for the visualization of 3D images, and greater motivation and interactive learning was demonstrated by students and teachers. Among the fundamental conclusions, the importance of illustrating thematic contents in which visualization is difficult, such as planets, organs of the human body, the cell, among others, and in general emphasize the importance of incorporating technological aspects Computer science in the different areas of knowledge, since these allow to generate significant learning experiences.